2014
DOI: 10.3390/nano4020267
|View full text |Cite
|
Sign up to set email alerts
|

Work Function Engineering of Graphene

Abstract: Graphene is a two dimensional one atom thick allotrope of carbon that displays unusual crystal structure, electronic characteristics, charge transport behavior, optical clarity, physical & mechanical properties, thermal conductivity and much more that is yet to be discovered. Consequently, it has generated unprecedented excitement in the scientific community; and is of great interest to wide ranging industries including semiconductor, optoelectronics and printed electronics. Graphene is considered to be a next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(161 citation statements)
references
References 167 publications
(217 reference statements)
2
158
0
1
Order By: Relevance
“…In this sense, the possibility of adjusting the work function through chemical functionalization makes graphene a very promising material in the semiconductor field. 29 Band-gap opening has been demonstrated after in situ doping, 30 chemical doping, 31 electrochemical doping 32 or BN doping of chemical vapor deposited graphene. 33 The WF of graphene can be tuned by using different methods, such as the electric field effect, 34 chemical doping with heteroatoms, 35 or chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the possibility of adjusting the work function through chemical functionalization makes graphene a very promising material in the semiconductor field. 29 Band-gap opening has been demonstrated after in situ doping, 30 chemical doping, 31 electrochemical doping 32 or BN doping of chemical vapor deposited graphene. 33 The WF of graphene can be tuned by using different methods, such as the electric field effect, 34 chemical doping with heteroatoms, 35 or chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…In case of HEL, the work function is found to be 4.9 eV, which is similar to the work function of graphene doped with AgNPs. Garg et al demonstrated that the work function of graphene could be tuned from 4.3 eV to 5.0 eV by introducing Ag [12]. According to Figure 3(b), we have encountered that the work function of GO can be easily tuned to a value lower or higher than that of ITO by being reduced with hydrazine or sandwiched with AgNPs, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Graphene is a zero band gap semimetal with a small overlap between its HOMO and LUMO [12][13][14]. In fact, the electrical, mechanical, optical, and thermal properties of graphene are very similar to those of single-walled carbon nanotubes (SWCNTs), while it can be prepared at significantly lower cost [11].…”
Section: Graphene Derivative Materialsmentioning
confidence: 99%